Efektivitas Rebozo Terhadap Penurunan Nyeri pada Persalinan Kala I - Aritonang, Tetty Rina; Intarti, Wiwit Desi; Ana, Amalia; Assajda, Ashwa; Fadiya, Eza; Nara, Nadya; Sallena, Rahel; Zulfa, Vina; Sianturi, Yulia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Background: Rebozo is a technique for giving space to the baby in a way that is pleasant for the mother. Rebozo can be used during labor to help the muscles and muscle fibers in the uterine ligaments relax so as to reduce pain during contractions. Objective: This study aims to determine the effect of rebozo on reducing pain in the first stage of labor. Research method: In preparing this review, the technique used was a literature study technique by searching for sources or literature in the form of primary data in the form of national journals for the last 4 years (2019- 2023). Research results: In mothers who used the rebozo technique, labor occurred more quickly compared to those who did not use the rebozo technique. Meanwhile, the pain level of primigravida mothers who use the rebozo technique is lower than those who do not use the rebozo technique.